Evangelization and Westernization in the Southern Border of the Kingdom of Chile. The Franciscans of the Colegio de Misiones de Chillán [Mission School of Chillán], XVIII c. - Cristián Eduardo Leal Pino; Andrés Alejandro Quitral Manosalva (Historia y Memoria, 2017)
This article aims at studying the participation of the Mission School of Chillán in the spiritual conquest of the indigenous communities of the sourthern border of the Kingdom of Chile towards the end of the Colony. Its purpose is to analyze the role accomplished by Seraphic friars in this time and place. Archival sources examined were mission reports, royal orders, travel diaries, letters, certifications and account books in the National Archive of Santiago de Chile. This information enabled us to determine the role played by the Santa Barbara hospice and the School of Naturals in the strategies of evangelization and westernization of indigenous communities. The hypothesis proposed is that until the second half of the XVIII century, in the sourthern border of the Kingdom of Chile, the missionaries of the School of Chillán developed not only a spiritual, but also a political role. Even though this role did not harvest the expected results for the Spanish Crown, it succeeded in generating spaces of communication between the hispanic-criollo authorities and indigenous groups at the border.